2021
DOI: 10.3390/ma14092329
|View full text |Cite
|
Sign up to set email alerts
|

Do Microplastics Enter Our Food Chain Via Root Vegetables? A Raman Based Spectroscopic Study on Raphanus sativus

Abstract: The outburst of plastic pollution in terrestrial ecosystems poses a potential threat to agriculture and food safety. Studies have already provided evidence for the uptake of plastic microparticles by several plant species, accompanied by numerous developmental effects, using fluorescence labelling techniques. Here, we introduce the implementation of confocal Raman spectroscopy, a label-free method, for the effective detection of microplastics (MPs) accumulation in the roots of a common edible root vegetable pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(20 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…They destroy the tertiary structure of pectin methylesterase in carrots, which is involved in the synthesis of cell wall components, contributing to the loss of the vegetable’s crunchiness. Microplastics reduce the nutritional value of Daucus carota and pose potential risks to human health [ 187 , 188 ].…”
Section: Contaminantsmentioning
confidence: 99%
See 1 more Smart Citation
“…They destroy the tertiary structure of pectin methylesterase in carrots, which is involved in the synthesis of cell wall components, contributing to the loss of the vegetable’s crunchiness. Microplastics reduce the nutritional value of Daucus carota and pose potential risks to human health [ 187 , 188 ].…”
Section: Contaminantsmentioning
confidence: 99%
“…Similarly to PS, it can enter the intercellular spaces of carrots [ 185 ]. In addition, ABS, through the small fissures from which radish lateral roots emerge, can penetrate the xylem vessels [ 188 ]. It has also been found that PS particles with a size of 100 nm affect the reduction in the root length of Raphanus sativus [ 188 ].…”
Section: Contaminantsmentioning
confidence: 99%
“…Raman spectroscopy analysis indicated exogenous accumulation and uptake of MPs by root vegetables such as radish has increased the concern of microplastic ingestion through food and higher amount of MPs reaching humans and is a threat to food safety and health concerns [43]. It has been revealed that MPs in aquatic animals lead to neurotoxicity in the brain so it might be possible that similar impacts can be observed in human brains [44].…”
Section: Conceivable Effects On Human Healthmentioning
confidence: 99%
“…Crop cultivation itself (the formation of the root system, the collection of crops such as potatoes and carrots), dry weather (the formation of cracks through which plastics move deeper), and the action of soil organisms also contribute to the spread of microplastics to the lower layers of the soil [102]. Accumulation and migration of micro-and nanoplastics was observed in a laboratory experiment with radish (Raphanus sativus) where acrylonitrile butadiene styrene powder was applied to the root system of the plant [103].…”
Section: Microplastic Contamination Of the Food Chainmentioning
confidence: 99%